Electronic testing system (ETS) / Shamsul Anwar Noor Ahmed Bashir - Shamsul Anwar, Noor Ahmed Bashir (2001)
The final year project is the qualification, which is required to complete the bachelor degree for all final year students of faculty of Computer Science and Information Technology, University Malaya. The purpose of this final year project is to expose students to the real working life of environment as well as getting experience in the real world project management. In this modern age of Information Technology, people are experiencing with the letter "E" which stands for Electronic. Such as, E-mail, E-commerce, E-government as well as E-test. The E-test stands for Electronic Testing, is a computer system, that can be applied in any educational institutions for the purpose of examination via computer. The main objective of this E-Test is to use it for taking the examination on the computer that cannot be done on papers, such as using multimedia or any other interactive knowledge-based questions. ETS has the capacity of generating randomized questions and answers in a large database of access, where students have to experience the E-test during their examination hours. The ETS is a modern way of testing system, where students have to sit for exam without carrying along with them any traditional testing instruments such as, paper, pen, pencil, and the unique characteristic of this system is to test something that cannot totally be done on papers. The purpose of developing this ETS is to make easier, secure and time saving testing system, in this modern computer age.